Effects of CO2-assisted high-pressure processing on microbiological and physicochemical properties of Chinese spiced beef. (March 2023) - Liu, Junmei; Yuan, Shuang; Han, Dong; Liu, Jiqian; Zhao, Laiyu; Wu, Jihong
Abstract: The objective of this study was to evaluate the effect of CO2 -assisted high-pressure processing (CO2 -HPP) on microbiological and physicochemical properties of Chinese spiced beef. The presence of CO2 induced extra reduction of Staphylococcus aureus, Escherichia coli and Listeria innocua under 150–450 MPa . The maximum extra reduction of S. aureus and E. coli were found at 450 MPa. The Listeria innocua cells were more resistant to CO2 -HPP than the Staphylococcus aureus and Escherichia coli cells . CO2 –450 MPa extended the shelf-life of Chinese spiced beef by one week than 450 MPa. CO2 –450 MPa didn't significantly increased the thiobarbituric acid reactive substances (TBARS) value of Chinese spiced beef compared with 450 MPa. CO2 –450 MPa limited 450 MPa induced color change. During cold storage, CO2 –450 MPa better maintained the firmness of Chinese spiced beef compared with 450 MPa, and the TBARS value of CO2 –450 MPa treated samples was significantly lower than 450 MPa-treated samples. Industrial relevance: High-pressure processing (HPP) is the most successful commercialized non-thermal technique in food industry, which could extend the shelf-life of Chinese spiced beef to 3 weeks. Nevertheless, HPP may induce color change, decrease firmness and increase lipid oxidation. Addition of carbon dioxide to HPP was shown to reduce lipid oxidation, limit color and texture changes, and slow down the growth of microorganisms in Chinese spiced beef during refrigerated storage. Our study determined the optimal condition. Furthermore, CO2 inflation can be achieved with commercially available modified atmosphere packaging machine. When CO2 -HPP is industrialized, in addition to safety and nutrient preservation, the shelf-life of products will also increase. Highlights: CO2 –450 MPa induced 1.4 and 1.8 more log units reduction of S. aureus and E. coli than 450 MPa-treated. The L. innocua cells was more resistant to CO2 -HPP than the S. aureus and E. coli. Addition of CO2 extended the shelf-life of 450 MPa-treated spiced beef by one week. CO2 -HPP limited HPP-induced color and texture changes, and reduced lipid oxidation. CO2 -HPP made up for the shortcomings of HPP in spiced beef (pH 6.35) applications.